PROTECTIVE EFFECT OF CHLORELLA VULGARIS ON DNA DAMAGE, OXIDATIVE STRESS, AND LUNG MORPHOLOGICAL CHANGES IN CIGARETTE SMOKE-EXPOSED RATS - Ks, Zamri; Mkn, Norripin; Fi, Darus; Dg, Ekambaram; Nd, Abdul Raof; Nh, Roslan; F, Ahmad; F, Mohammed; S, Makpol; Ya, Mohd Yusof (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to determine the protective effect of Chlorella vulgaris (ChV), antioxidant-rich unicellular green alga, and in cigarette smoke-exposed rats. Methods: Male Sprague Dawley rats were divided into 4 groups: Control Group (C), ChV group (300 mg/kg body weight), cigarette smoke-exposed (S) group, and S group treated with ChV (S+ChV). Blood samples were drawn from the orbital sinus on days 0, 15, and 30 for the determination of DNA damage by Comet assay and plasma malondialdehyde (MDA) using high-performance liquid chromatography. Rats were killed on day 30, and lung tissue samples were taken for the evaluation of airspace enlargement and number of inflammatory cells. Results: Increased DNA damage (1004.8 au + 329.2, day 15; 1102.7 + 197.8, day 30) and high MDA levels (10.66 + 0.27, day 15; 10.29 + 0.9 day 30) were found in cigarette smoke-exposed rats on days 15 and 30 but were reduced significantly (p<0.05) when treated with ChV (DNA: 482.6 + 223.3, day15; 423.5 + 74.6, day 30 and MDA: 6.1 + 0.6, day15; 6.6 + 2.5, day 30) for both days. Hematoxylin and eosin staining showed that cigarette smoke-exposed rats had high frequency of airspace enlargement and number of inflammatory cells which were reduced when treated with ChV. Conclusion: ChV has a protective role in cigarette smoke-exposed rats by reducing oxidative DNA damage, MDA levels, lung cells inflammation, and airspace enlargement.